Hegemoni Jawa Mataraman dalam Tari Soreng sebagai Ikon Budaya Kabupaten Magelang - Sukarjo Waluyo (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2019)
The problem of locality and local wisdom in Indonesia became a problem that received a lot of attention after the 1998 reform. Government in the New Order era which was previously centralized and centralized in Jakarta turned into decentralized with the concept of regional autonomy. Some districts and cities in Central Java began to identify the rich history, local arts and culture to be appointed as regional icons. Magelang regency made the Soreng dance from Ngablak District a typical dance of a cultural icon. Soreng Dance tells the story of one of the historical figures in Java, namely Arya Penangsang. Characterization of the Arya Penangsang in the Soreng dance which take the source of the story from the Babad Tanah Djawi represent a form of representation of the Javanese ruler of Mataraman, namely the Sultanate of Pajang which was passed on by the Sultanate of Mataram and its heirs (Surakarta Palace, Yogyakarta Palace, Mangkunegaran, and Pakualaman) for the benefit of hegemony. The results of this study reveal that representation is used by several parties concerned with the figure of Arya Penangsang, namely: 1) Babad Tanah Djawi / Javanese Mataraman culture manifested in Soreng dance art; 2) Soreng dance depicts Arya Penangsang as a rude and power-hungry figure, defeated by a very young child, and his territory (Jipang) is despised by the Pajang Sultanate because it is seen as a rebel; 3) Soreng dance strengthens the representation of hegemony-style Babad Tanah Djawi/Javanese Mataraman culture.